Preparation method of tin-antimony-titanium anode with new matrix structure
Through the solid connection between the sol-gel method and the porous titanium matrix, the problems of short service life of the tin antimony anode and high-temperature sintering deformation are solved, and the good bonding of the tin antimony oxide and the matrix are achieved and the significant improvement of the electrode life is achieved.
Patent Information
- Application Number
- CN202211161514.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-09-22
AI Technical Summary
The existing tin antimony anode has a short service life and the porous titanium matrix is prone to deform during high temperature sintering, which affects the electrode performance and stability.
The tin antimony coating is prepared by sol-gel method. Through the solid connection between the support and porous titanium, the pore size and sintering conditions are adjusted, the flatness and structure of the matrix are ensured, the volatility of tin antimony is reduced, and the sintering is carried out through multiple high-temperature sintering. Increase coating thickness.
The bonding force and tin antimony oxide with the matrix are significantly improved, the service life of the electrode is extended, and deformation problems during high-temperature sintering are avoided.
Smart Images

Figure CN115433952B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the fields of environmental protection technology and electrochemical technology, and specifically relates to a method for preparing a tin-antimony-titanium anode with a new matrix structure. Background Art
[0002] Among the existing sewage treatment methods, advanced oxidation technology, especially ozone catalytic oxidation technology, has shown great potential in solving water pollution, especially in treating organic matter in water. It has attracted much attention due to its advantages such as high electrolysis efficiency, fast reaction time and no secondary pollution.
[0003] The key to the electrolytic ozone production lies in the anode reaction. Commonly used anodes are mainly lead dioxide anodes and tin antimony anodes. During the electrolysis process of lead dioxide anodes, lead dioxide will gradually dissolve in the aqueous solution, causing secondary pollution. Compared with lead dioxide anodes, tin antimony anodes have higher oxygen evolution potential and are pollution-free, but their service life is shorter.
[0004] Common tin-antimony anodes mainly use titanium plates or titanium meshes as the substrate, and increase their specific surface area through sandblasting to increase the tin-antimony loading and improve the service life of the tin-antimony anode. However, because tin-antimony salts are highly volatile during the oxidation process, it is difficult to prepare tin-antimony oxide titanium anodes with longer life through oxidation methods.
[0005] Porous titanium itself has a large specific surface area, so it can also be used as a matrix in the preparation of tin-antimony anodes. However, porous titanium is easily deformed after high-temperature sintering. In mild cases, it affects the inter-electrode distance between the cathode and the anode. In severe cases, the deformation may render the workpiece unusable. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a tin-antimony-titanium anode with a new matrix structure, which solves the problems of short service life of the tin-antimony anode prepared by the prior art and easy deformation of the porous titanium matrix sintered at high temperature.
[0007] The technical solution adopted by the present invention is a method for preparing a tin-antimony-titanium anode with a new matrix structure, and the specific steps are as follows:
[0008] Step 1, connecting the support body and porous titanium to form a matrix, and cleaning and drying the matrix; adding tin salt, antimony salt and additives into a reactor, adjusting the solution pH to 1-3, the temperature to 30°C-60°C, reacting for 5h-15h to obtain a crude product, allowing the prepared crude product to stand for polymerization at room temperature, and taking the upper clear liquid as a coating solution for standby use;
[0009] Step 2, completely immersing the substrate dried in step 1 in the coating solution, then taking out the substrate, and allowing the coating solution on the substrate surface to dry naturally to obtain a porous titanium material coated with a Sn-Sb coating;
[0010] Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace for high-temperature sintering treatment;
[0011] Step 4: Repeat steps 2 and 3 for multiple times until the required coating thickness is obtained.
[0012] The present invention is also characterized in that
[0013] In step 1, the pore size of the porous titanium is 100 μm to 500 μm, the support body is one of titanium wire, titanium rod, titanium mesh or titanium strip, and the support body and the porous titanium are fixed to each other by welding.
[0014] In step 1, the substrate is cleaned by pickling with 10% oxalic acid solution at a temperature of 90°C to 100°C for 60min to 90min. After pickling, the substrate is further cleaned by ultrasound for 20min to 40min.
[0015] The drying in step 1 is specifically air drying or drying in a drying oven, the temperature of the drying oven is 100° C. to 120° C., and the drying time is 20 min to 30 min.
[0016] In step 1, the tin salt is a metal alkoxide or a chloride salt, the antimony salt is a metal alkoxide or a chloride salt, and the mass ratio of the tin salt to the antimony salt is tin salt:antimony salt=10:0.8-1.2.
[0017] In step 1, the additive is a strong oxidant, a stabilizer or a dispersant, the strong oxidant is one of perchloric acid, sodium perchlorate, calcium peroxide or barium peroxide, the stabilizer is one of epoxy fatty acid, polyol or polyvinyl alcohol, and the dispersant is one of n-butanol, isopropanol, ethylene glycol or ethanol;
[0018] The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.1-0.2:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.001-0.005:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=15-20:1.
[0019] In step 2, when the pore size of the porous titanium is 100 μm to 300 μm, vacuum immersion is used, the vacuum immersion time is 2 min to 5 min, and the vacuum degree is 1×10 2 Pa~1×10 5 Pa.
[0020] In step 2, when the pore size of the porous titanium is 301 μm to 500 μm, normal pressure immersion is adopted, and the normal pressure immersion time is 5 min to 10 min.
[0021] In step 3, the high temperature sintering temperature is 500° C. to 700° C., and the sintering time is 15 min to 20 min.
[0022] The beneficial effects of the present invention are:
[0023] (1) The preparation method of the present invention fixes the porous titanium to the support body, which can ensure the specific surface area of the substrate while satisfying its structural and flat properties, thereby avoiding deformation of the porous titanium during high-temperature sintering.
[0024] (2) The preparation method of the present invention adopts the sol-gel method to prepare the tin-antimony coating, which greatly reduces the volatility of tin-antimony and cooperates with the substrate of the fixed support body to greatly improve the binding force between the tin-antimony oxide and the substrate and the tin-antimony loading, further improving the service life of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 1 and 2 are LSV diagrams of Example 1, Example 4 and the comparative example of the present invention. DETAILED DESCRIPTION
[0026] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] The preparation method of a novel matrix structure tin-antimony-titanium anode of the present invention is specifically implemented according to the following steps:
[0028] Step 1, connecting the support body and porous titanium to form a matrix by welding, ensuring the specific surface area of the matrix while satisfying its structural and flatness, avoiding deformation of the porous titanium during the subsequent high-temperature sintering process; the pore size of the porous titanium is 100μm~500μm, and the support body is a titanium skeleton with a supporting function such as titanium wire, titanium rod, titanium mesh and titanium bar, and then the connected matrix is pickled with an oxalic acid solution with a concentration of 10%, the temperature during pickling is 90℃~100℃, the time is 60min~90min, and after pickling, the matrix is continuously cleaned with ultrasound, and the cleaning time is 20min~40min; after cleaning, air-dry or dry in a drying oven, the temperature of the drying oven is 100℃~120℃, and the drying time is 20min~30min.
[0029] Add tin salt, antimony salt and additives into a four-necked bottle equipped with a thermometer and a stirrer, adjust the pH value of the solution to 1-3, the mass ratio of tin salt to antimony salt is tin salt: antimony salt = 10: 0.8-1.2, and the tin salt and antimony salt are metal alkoxides or chlorides, respectively.
[0030] The additive is a strong oxidant, a stabilizer or a dispersant, the strong oxidant is one of perchloric acid, sodium perchlorate, calcium peroxide and barium peroxide, the stabilizer is one of epoxy fatty acid, polyol and polyvinyl alcohol, and the dispersant is one of n-butanol, isopropanol, ethylene glycol and ethanol;
[0031] The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.1-0.2:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.001-0.005:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=15-20:1;
[0032] The reaction temperature in the reactor is then adjusted to 30°C to 60°C, and the reaction is carried out for 5h to 15h to obtain a crude product. The prepared crude product is allowed to stand for polymerization at room temperature, and the upper clear liquid is taken as a coating liquid for later use.
[0033] Step 2: completely immerse the substrate dried in step 1 in the coating solution. When the pore size of the porous titanium is 100 μm to 300 μm, vacuum immersion is adopted. The vacuum immersion time is 2 min to 5 min, and the vacuum degree is 1×10 2 Pa~1×10 5 When the pore size of the porous titanium is 301 μm to 500 μm, it is immersed at normal pressure for 5 to 10 minutes, and then the substrate is taken out, and the coating liquid on the surface of the substrate is naturally air-dried to obtain a porous titanium material coated with a Sn-Sb coating.
[0034] Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace at a temperature of 500° C. to 700° C. for 15 min to 20 min for high-temperature sintering.
[0035] Step 4: Repeat steps 2 and 3 for multiple times until the required coating thickness is obtained. The coating thickness is preset in advance according to the requirements.
[0036] The preparation method of the present invention adopts the sol-gel method to prepare the tin-antimony coating, which greatly reduces the volatility of tin-antimony, and cooperates with the substrate of the fixed support body to greatly improve the binding force between the tin-antimony oxide and the substrate and the tin-antimony loading, further improving the service life of the electrode.
[0037] Example 1
[0038] Step 1, select titanium wire and porous titanium with a pore size of 100 μm to weld to form a substrate, use a 10% oxalic acid solution to pickle the substrate at a temperature of 90°C and a time of 90 minutes. After pickling, use ultrasound to continue cleaning the surface of the substrate for 20 minutes; and air dry after cleaning.
[0039] Add tin salt, antimony salt and additives into the reactor, adjust the pH value of the solution to 1, both tin salt and antimony salt are metal alkoxides, the mass ratio of tin salt to antimony salt is tin salt: antimony salt = 10:0.8, the strong oxidant is perchloric acid, the stabilizer is epoxy fatty acid, and the dispersant is n-butanol;
[0040] The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.1:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.001:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=15:1;
[0041] The reaction temperature in the reactor was adjusted to 30° C. and the reaction was carried out for 15 hours to obtain a crude product. The prepared crude product was allowed to stand for polymerization at room temperature and the upper clear liquid was taken as a coating liquid for later use.
[0042] Step 2: completely immerse the substrate dried in step 1 in the coating solution by vacuum immersion for 2 min at a vacuum degree of 1×10 5 Pa, then take out the substrate, and wait for the coating liquid on the substrate surface to dry naturally to obtain a porous titanium material coated with a Sn-Sb coating.
[0043] Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace at a temperature of 500° C. for 20 minutes for high-temperature sintering treatment.
[0044] Step 4: Repeat steps 2 and 3 15 times to obtain a new substrate structure tin-antimony-titanium anode that meets the required coating thickness.
[0045] Example 2
[0046] Step 1, select a titanium rod and a porous titanium with a pore size of 200 μm to weld to form a substrate, use a 10% oxalic acid solution to pickle the substrate, the pickling temperature is 94°C, the time is 80 minutes, and after pickling, the substrate is further cleaned by ultrasound for 25 minutes; and dried in a drying oven, the oven temperature is 100°C, and the drying time is 30 minutes.
[0047] Add tin salt, antimony salt and additives into the reactor, adjust the pH value of the solution to 2, the tin salt is metal alkoxide, the antimony salt is chloride salt, the mass ratio of tin salt to antimony salt is tin salt: antimony salt = 10:0.9, the strong oxidant is sodium perchlorate, the stabilizer is polyol, and the dispersant is isopropanol;
[0048] The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.14:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.002:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=16:1;
[0049] The reaction temperature in the reactor was adjusted to 40° C. and the reaction was carried out for 12 hours to obtain a crude product. The prepared crude product was allowed to stand for polymerization at room temperature and the upper clear liquid was taken as a coating liquid for later use.
[0050] Step 2: completely immerse the substrate dried in step 1 in the coating solution by vacuum immersion for 3 min at a vacuum degree of 1×10 3Pa, then take out the substrate, and wait for the coating liquid on the substrate surface to dry naturally to obtain a porous titanium material coated with a Sn-Sb coating.
[0051] Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace at a temperature of 600° C. for 18 minutes for high-temperature sintering.
[0052] Step 4: Repeat steps 2 and 3 10 times to obtain a new substrate structure tin-antimony-titanium anode that meets the required coating thickness.
[0053] Example 3
[0054] Step 1, select a titanium mesh and a porous titanium with a pore size of 300 μm to weld to form a substrate, use a 10% oxalic acid solution to pickle the substrate, the pickling temperature is 98°C, the time is 70 minutes, and after pickling, the surface of the substrate is continuously cleaned by ultrasound for 35 minutes; and dried in a drying oven, the oven temperature is 110°C, and the drying time is 25 minutes.
[0055] Add tin salt, antimony salt and additives into the reactor, adjust the pH value of the solution to 2, the tin salt is chloride salt, the antimony salt is metal alkoxide, the mass ratio of tin salt to antimony salt is tin salt: antimony salt = 10:1.1, the strong oxidant is calcium peroxide, the stabilizer is polyvinyl alcohol, and the dispersant is ethylene glycol;
[0056] The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.18:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.004:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=18:1;
[0057] The reaction temperature in the reactor was adjusted to 50° C. and the reaction was carried out for 8 hours to obtain a crude product. The prepared crude product was allowed to stand for polymerization at room temperature and the upper clear liquid was taken as a coating liquid for later use.
[0058] Step 2: completely immerse the substrate dried in step 1 in the coating solution by vacuum immersion for 2 min at a vacuum degree of 1×10 5 Then the substrate is taken out, and the coating liquid on the surface of the substrate is naturally air-dried to obtain a porous titanium material coated with a Sn-Sb coating.
[0059] Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace at a temperature of 600° C. for 17 minutes for high-temperature sintering treatment.
[0060] Step 4: Repeat steps 2 and 3 12 times to obtain a new substrate structure tin-antimony-titanium anode that meets the required coating thickness.
[0061] Example 4
[0062] Step 1, select a titanium bar and a porous titanium with a pore size of 500 μm to weld to form a substrate, use a 10% oxalic acid solution to pickle the substrate, the pickling temperature is 100°C, the time is 60 minutes, and after pickling, the surface of the substrate is continuously cleaned by ultrasound for 40 minutes; and dried in a drying oven, the oven temperature is 120°C, and the drying time is 20 minutes.
[0063] Add tin salt, antimony salt and additives into the reactor, adjust the solution pH to 2, both tin salt and antimony salt are chloride salts, the mass ratio of tin salt to antimony salt is tin salt: antimony salt = 10:1.2, the strong oxidant is barium peroxide, the stabilizer is polyvinyl alcohol, and the dispersant is ethanol;
[0064] The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.2:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.005:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=20:1;
[0065] The reaction temperature in the reactor was adjusted to 60° C. and the reaction was carried out for 5 hours to obtain a crude product. The prepared crude product was allowed to stand for polymerization at room temperature and the upper clear liquid was taken as a coating liquid for later use.
[0066] Step 2, completely immerse the substrate dried in step 1 in the coating solution at normal pressure for 5 minutes, then take out the substrate, and wait for the coating solution on the substrate surface to dry naturally to obtain a porous titanium material coated with a Sn-Sb coating.
[0067] Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace at a temperature of 700° C. for 15 minutes for high-temperature sintering treatment.
[0068] Step 4: Repeat steps 2 and 3 12 times to obtain a new substrate structure tin-antimony-titanium anode that meets the required coating thickness.
[0069] Example 5
[0070] Step 1, select a titanium bar and a porous titanium with a pore size of 400 μm to weld to form a substrate, use a 10% oxalic acid solution to pickle the substrate, the pickling temperature is 100°C, the time is 60 minutes, and after pickling, the surface of the substrate is continuously cleaned by ultrasound for 40 minutes; and dried in a drying oven, the oven temperature is 120°C, and the drying time is 20 minutes.
[0071] Add tin salt, antimony salt and additives into the reactor, adjust the solution pH to 2, both tin salt and antimony salt are chloride salts, the mass ratio of tin salt to antimony salt is tin salt: antimony salt = 10:1.2, the strong oxidant is barium peroxide, the stabilizer is polyvinyl alcohol, and the dispersant is ethanol;
[0072] The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.2:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.005:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=20:1;
[0073] The reaction temperature in the reactor was adjusted to 60° C. and the reaction was carried out for 5 hours to obtain a crude product. The prepared crude product was allowed to stand at room temperature and the upper clear liquid was taken as a coating liquid for later use.
[0074] Step 2, completely immerse the substrate dried in step 1 in the coating solution at normal pressure for 10 minutes, then take out the substrate, and wait for the coating solution on the surface of the substrate to dry naturally to obtain a porous titanium material coated with a Sn-Sb coating.
[0075] Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace at a temperature of 700° C. for 15 minutes for high-temperature sintering treatment.
[0076] Step 4, repeat steps 2 and 3 11 times to obtain a new substrate structure tin-antimony-titanium anode that meets the required coating thickness.
[0077] Example 6
[0078] Step 1, select a titanium bar and a porous titanium with a pore size of 450μm to weld to form a substrate, use a 10% oxalic acid solution to pickle the substrate, the pickling temperature is 92°C, the time is 65min, and after pickling, the surface of the substrate is continuously cleaned by ultrasound for 33min; and the substrate is dried in a drying oven at a temperature of 112°C for 21min.
[0079] Add tin salt, antimony salt and additives into the reactor, adjust the solution pH to 2, both tin salt and antimony salt are chloride salts, the mass ratio of tin salt to antimony salt is tin salt: antimony salt = 10:1.2, the strong oxidant is barium peroxide, the stabilizer is polyvinyl alcohol, and the dispersant is ethanol;
[0080] The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.2:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.005:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=20:1;
[0081] The reaction temperature in the reactor was adjusted to 60° C. and the reaction was carried out for 5 hours to obtain the desired crude product. The prepared crude product was allowed to stand at room temperature and the upper clear liquid was taken as a coating liquid for later use.
[0082] Step 2, completely immerse the substrate dried in step 1 in the coating solution at normal pressure for 8 minutes, then take out the substrate, and wait for the coating solution on the surface of the substrate to dry naturally to obtain a porous titanium material coated with a Sn-Sb coating.
[0083] Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace at a temperature of 620° C. for 16 minutes for high-temperature sintering.
[0084] Step 4: Repeat steps 2 and 3 for 6 times to obtain a new substrate structure tin-antimony-titanium anode with a coating thickness that meets the requirements of its use.
[0085] Comparative Example
[0086] Step 1, take a porous titanium plate as a substrate, put the substrate into an oxalic acid solution at 100°C, pickle for 1.5 hours, and then clean it with pure water; then place it in an ultrasonic cleaner for cleaning for 30 minutes, take it out and dry it for use; add tin tetrachloride, antimony chloride and a mixed solution into a beaker and stir evenly to obtain a coating solution, the mass ratio of tin tetrachloride, antimony chloride and the mixed solution is tin tetrachloride: antimony chloride: mixed solution = 10:1:18; the mixed solution is n-butanol and isopropanol in a mass ratio of 1:1.
[0087] Step 2, apply the coating liquid prepared in step 1 to the surface of the substrate, and then place the substrate in a high-temperature furnace for sintering at a temperature of 450° C. for 10 minutes, and repeat 20 times.
[0088] like Figure 1 As shown, Example 1, Example 4 and the comparative example were tested. The comparative example is a traditional preparation process for preparing tin-antimony anode. It was measured that the oxygen evolution potentials thereof were all above 1.3 V, which met the potential requirement for preparing ozone.
[0089] The products obtained in Examples 1 to 6 and the comparative example were placed in an acidic environment and loaded with 2WA / m 2 The service life is tested with a current of , and the test results are shown in Table 1;
[0090] Table 1 Service life test in acidic environment
[0091]
[0092]
[0093] The products obtained in Examples 1 to 6 and the comparative example were placed in a common water environment and loaded with a voltage of 10V to test their service life. The test results are shown in Table 2.
[0094] Table 2 Service life test in common water environment
[0095] Product Number Lifespan Example 1 22d Example 2 21.5d Example 3 21d Example 4 20d Example 5 19.8d Example 6 20.2d Comparative Example 3d
[0096] Combining the data in Table 1 and Table 2, it can be seen that the service life of Examples 1 to 6 in an acidic environment or a common water environment far exceeds the service life of the anode prepared in the comparative example, proving that the service life of the tin-antimony-titanium anode prepared by this method is significantly improved, and the preparation process of this method is simple and suitable for large-scale production.
[0097] In order to better illustrate that the tin-antimony-titanium anode prepared by the present invention is not easily deformed after high-temperature sintering, the flatness of Examples 1 to 6 and the comparative example before and after high-temperature sintering was measured, and the measured data are shown in Table 3:
[0098] Table 3 Flatness before and after high temperature sintering
[0099]
[0100] As shown in Table 3, the flatness of Examples 1 to 6 and the comparative example before sintering was 0.2 mm. After high-temperature sintering, the change in flatness of Examples 1 to 6 was significantly smaller than that of the comparative example, further proving that the tin-antimony-titanium anode prepared by the present invention is not easily deformed after high-temperature sintering.
Claims
1. A method for preparing a tin-antimony-titanium anode with a new matrix structure, characterized in that: The specific steps are as follows: Step 1, connecting the support body and porous titanium to form a matrix, and cleaning and drying the matrix; adding tin salt, antimony salt and additives into a reactor, adjusting the solution pH to 1-3, the temperature to 30°C-60°C, reacting for 5h-15h to obtain a crude product, allowing the prepared crude product to stand for polymerization at room temperature, and taking the upper clear liquid as a coating solution for standby use; Step 2, completely immersing the substrate dried in step 1 in the coating solution, then taking out the substrate, and allowing the coating solution on the substrate surface to dry naturally to obtain a porous titanium material coated with a Sn-Sb coating; Step 3, placing the porous titanium material coated with the Sn-Sb coating obtained in step 2 in a high-temperature furnace for high-temperature sintering treatment; Step 4, repeating steps 2 and 3 for multiple times until a coating thickness that meets the requirements is obtained; The support body and the porous titanium are fixedly connected to each other by welding; In step 1, the tin salt is a metal alkoxide or a chloride salt, the antimony salt is a metal alkoxide or a chloride salt, and the mass ratio of the tin salt to the antimony salt is tin salt: antimony salt = 10: 0.8-1.2; The additives in step 1 are a strong oxidant, a stabilizer and a dispersant, wherein the strong oxidant is one of perchloric acid, sodium perchlorate, calcium peroxide or barium peroxide, the stabilizer is one of epoxy fatty acid, polyol or polyvinyl alcohol, and the dispersant is one of n-butanol, isopropanol, ethylene glycol or ethanol; The mass ratio of the strong oxidant to the tin salt is strong oxidant:tin salt=0.1-0.2:1, the mass ratio of the stabilizer to the tin salt is stabilizer:tin salt=0.001-0.005:1, and the mass ratio of the dispersant to the tin salt is dispersant:tin salt=15-20:
1.
2. The method for preparing a novel matrix structure tin-antimony-titanium anode according to claim 1, characterized in that: In step 1, the pore size of the porous titanium is 100 μm to 500 μm, and the support is one of titanium wire, titanium rod, titanium mesh or titanium strip.
3. The method for preparing a novel matrix structure tin-antimony-titanium anode according to claim 1, characterized in that: In the step 1, the substrate is cleaned by pickling with an oxalic acid solution having a concentration of 10%, the temperature of the pickling is 90°C to 100°C, and the time is 60min to 90min. After the pickling, the substrate is further cleaned by ultrasound for a cleaning time of 20min to 40min.
4. The method for preparing a novel matrix structure tin-antimony-titanium anode according to claim 1, characterized in that: The drying in step 1 is specifically air drying or drying in a drying oven, the temperature of the drying oven is 100° C. to 120° C., and the drying time is 20 min to 30 min.
5. The method for preparing a novel matrix structure tin-antimony-titanium anode according to claim 1, characterized in that: In step 2, when the pore size of the porous titanium is 100 μm to 300 μm, vacuum immersion is adopted, the vacuum immersion time is 2 min to 5 min, and the vacuum degree is 1×10 2 Pa ~1×10 5 Pa.
6. The method for preparing a novel matrix structure tin-antimony-titanium anode according to claim 1, characterized in that: In the step 2, when the pore size of the porous titanium is 301 μm to 500 μm, normal pressure immersion is adopted, and the normal pressure immersion time is 5 min to 10 min.
7. The method for preparing a novel matrix structure tin-antimony-titanium anode according to claim 1, characterized in that: In the step 3, the high temperature sintering temperature is 500° C. to 700° C., and the sintering time is 15 min to 20 min.
